Evaluation of antidepressant-like effect of hydroalcoholic extract of Passiflora incarnata in animal models of depression in male mice - Jafarpoor Nima; Abbasi-Maleki Saeid; Asadi-Samani Majid; Khayatnouri Mir Hadi (Shahrekord University of Medical Sciences, 2014)
Introduction: Passiflora incarnata (PI) is one of the commonest herbal anti-anxiety and sedative agents. The aim of the present study was to investigate the antidepressant effect of hydroalcoholic extract of PI in forced swim test (FST) and tail suspension test (TST) in male mice. Methods: In this experimental study, 48 male mice were randomly divided into 6 groups of 8: Negative and positive control groups received normal saline (10 ml/kg), fluoxetine (20 mg/kg) and imipramine (30 mg/kg), respectively and treatment groups received extracts of PI (200, 400 and 800 mg/kg). Immobility, swimming and climbing behaviors were recorded during 6-min. Results: All doses of PI extract compared to control group significantly reduced the duration of immobility time in both of two tests (p<0.001). Also, these extracts increased swimming time (p<0.001) without significant change of climbing time. Conclusion: PI has considerable antidepressant-like effect in animal models of depression. However, further studies are needed to determine its exact mechanism of action.